Mathematical Critical Thinking Skill: A Bibliometric Analysis Based on Vos Viewer Bibliometric - Nurhasanah, Nurhasanah; Tahmir, Suradi; Azizah, Rifdah; Jufri, Hasrini (EDUPEDIA Publisher, 2025)
This bibliometric analysis aims to see the opportunities and development of research trends related to mathematical critical thinking skills from 2019 to 2024. Through a bibliometric approach, this research will map publication trends based on the Scopus database by using Vos Viewer to analyze the data. The results of this study show the most publications and citations in 2020 as many as 55 publications and 777 citations, and a decrease in publications and citations from 2021 to 2024. Terms that are often related to mathematical critical thinking skills are students, problems, critical thinking, mathematics, and STEM.